2007
DOI: 10.1080/02841850701199967
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography of brain tumors: preliminary results

Abstract: MRE could be used as an imaging technique for noninvasive assessment of the consistency of brain tumor in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 9 publications
1
92
0
1
Order By: Relevance
“…Although many of these studies have shown that tumors are stiffer than normal brain (Xu et al, 2007;Scholz et al, 2007Scholz et al, , 2005Chauvet et al, 2015), some have shown the opposite (Reiss- Zimmermann et al, 2015;Streitberger et al, 2014), and determination of stiffness differences between tumor grades has been inconclusive using this technique. Consistent with observations of stiffening of brain tumors, increased diffusion of water within a tumor, as measured by magnetic resonance imaging (MRI), is prognostic of poor outcome and is correlated with increased expression of ECM genes whose products are expected to stiffen a tissue (Pope et al, 2012(Pope et al, , 2009.…”
Section: Mechanical Properties Of Brain Tumor Subtypesmentioning
confidence: 99%
“…Although many of these studies have shown that tumors are stiffer than normal brain (Xu et al, 2007;Scholz et al, 2007Scholz et al, , 2005Chauvet et al, 2015), some have shown the opposite (Reiss- Zimmermann et al, 2015;Streitberger et al, 2014), and determination of stiffness differences between tumor grades has been inconclusive using this technique. Consistent with observations of stiffening of brain tumors, increased diffusion of water within a tumor, as measured by magnetic resonance imaging (MRI), is prognostic of poor outcome and is correlated with increased expression of ECM genes whose products are expected to stiffen a tissue (Pope et al, 2012(Pope et al, , 2009.…”
Section: Mechanical Properties Of Brain Tumor Subtypesmentioning
confidence: 99%
“…In other applications, MRE has been found to have promise for differentiating benign breast lesions from malignant tumors [16,17]. Aside from one publication describing MRE of the brain tumors [18], there have been few reports of the use of MRE to evaluate masses in other parts of the body.…”
Section: Introductionmentioning
confidence: 99%
“…4,11,14,30,32,59,62 Promising modalities for predicting tumor consistency include MR imaging or ultrasound elastography. 44,60,61 In the future, a priori knowledge of tumor consistency may lend major support to the selection of a skull base approach from above versus below and warrants further research.…”
Section: Lateral Extension Beyond the Cavernous Sinusmentioning
confidence: 99%